Implementasi Manajemen Organisasi Intra Sekolah (OSIS) di SMA Daarul Ahsan Kecamatan Jayanti Kabupaten Tangerang - Fauzi, Anis; Subekhan, Moch.; Roni, Ahmad (Literasi: Jurnal Pendidikan Guru Indonesia, 2023)
This study aims to find out how the role and function of the student council at Daarul Ahsan High School, as well as how the implementation of Intra-School Organization Management (OSIS) at Darul Ahsan High School. The research method used is a descriptive qualitative method. Data collection techniques in this study used observation and interviews. The subjects of this study were the principal, student council supervisors who totaled 1 person, student council administrators who totaled 4 people and Daarul Ahsan high school students who numbered 5 people. His research methods use qualitative research. The data analysis technique used is the drawing of conclusions about the implementation of the organization's management. The results of the research obtained that the role of the student council based on the activity program is an effort to carry out coaching to students this effort is continuous so that students continue to have a good attitude in their daily lives which later students can have good morals and behavior so that students have provisions in carrying out life at the next level and can participate in the community / environment.